Current status of ultrasound training in obstetrics and gynecology: a scoping literature review - Matschl, Julia; Jimenez-Cruz, Jorge; Schäfer, Valentin Sebastian; Wittek, Agnes; Berg, Christoph; Geipel, Annegret; Gembruch, Ulrich; Strizek, Brigitte; Recker, Florian (Frontiers in Medicine, 2024)
As a widely accessible, cost-effective, and safe imaging tool, obstetric and gynecologic (OB/GYN) ultrasound (ULS) plays a vital role in diagnostics and patient care. With its growing relevance, the demand for comprehensive education in this field increases. The objective of this work was to outline the current state of OB/GYN ULS education. Method A scoping literature search was performed until May 2023 using the medical database PubMed according to PRISMA guidelines. Using specific keywords, relevant publications were filtered. Subsequently, abstracts were independently reviewed by two authors and the inclusion of each publication was assessed against pre-defined key search terms. Full-text versions of the included publications were scrutinized and pertinent information was extracted.In this review, 126 articles from the literature search matched the inclusion criteria and were investigated. Our findings revealed a diverse range of course concepts and programs, a lot of them not meeting the expectations of trainees and international guidelines. OB/GYN ULS training primarily targets residents, yet opportunities for early exposure and continuing education are underexplored. International organizations, such as the International Society of Ultrasound in Obstetrics and Gynecology (ISUOG) and the German Society for Ultrasound in Medicine (DEGUM) have proposed guidelines and curricula for standardized training. However, adoption remains varied. There's an emergent need to innovate teaching methods.There is consensus that standardizing OB/GYN ULS curricula could enhance training quality and streamline the creation of new programs, ultimately improving patient care. Further research is needed to define the most effective strategies for curriculum development and implementation.